Adequate levels of dietary digestible lysine improve growth, feed utilization and carcass composition but do not affect muscle morphology of tambaqui (Colossoma macropomum) juveniles - Martins, Graciela P.; Mazini, Bruno S.M.; Campos, Milena A.F.; Oliveira, Denise S.; Bueno, Guilherme W. [UNESP]; Camargo, Tavani R. [UNESP]; Guimarães, Igo G. (Elsevier, 2024)
The aim of this study was to determine the lysine requirement for tambaqui and estimate other essential amino acids (EAA) requirement based on the ideal protein concept. A total of 144 tambaqui juveniles (184.1 g ± 1.96) were randomly assigned into 18 500 L-aquaria connected to a water recirculation system. The experiment was performed in a completely randomized design with six treatments and three replicates. A basal control diet (52.5 g of protein kg−1 dry matter) was supplemented with six levels of synthetic lysine (9, 12, 15, 18, 21, and 24 g kg−1 diet). Then, a dose-response trial was conducted to determine the optimal level of lysine for enhancing fish growth and nutrient utilization. Additional analyses were carried out to understand and correlate the fish responses to the dietary lysine levels, including blood chemistry analysis, enzymatic activity, and muscle development patterns. Weight gain increased until reaching 2.27 g at 17.4 g kg−1 diet lysine. Protein (25.6 g) and lysine (55.6 g) retention plateaued at 18 g kg−1 lysine. The lipid concentration declined linearly (P < 0.001, R2 = 0.81) according to the increase in dietary lysine levels. Plasma ammonia and alanine aminotransferase activity decreased as lysine levels increased (P < 0.05, R2 = 0.95, 0.84, respectively). No differences were observed for muscle morphology. Regardless the dietary lysine levels, the predominance of muscle growth was via hypertrophy. In sum, the estimated lysine requirement based on weight gain for tambaqui was 17.4 g kg−1 diet or 54.37 g kg−1 of dietary protein.
Keywords: Essential amino acid; Fish; Growth; Lysine; Nutritional requirement; Reference amino acid